Resilient Surveillance Architecture for Critical Maritime Routes: A Case Study of the Strait of Malacca under Extreme Weather Scenarios - Oktaviandra, Yosyea; Asep Iwa Soemantri; Anwar Kurniadi (International Journal of Education, Vocational and Social Science, 2025)
The Strait of Malacca is one of the world's most critical maritime routes, serving as a key conduit between the Indian and Pacific Oceans. However, this strategic corridor faces increasing threats from extreme weather events such as tropical storms, heavy rainfall, and high waves driven by climate change. These conditions severely limit the effectiveness of traditional maritime surveillance systems that rely heavily on radar and satellite technologies, which often fail under adverse weather. This study proposes the concept of a Resilient Surveillance Architecture (RSA) an adaptive monitoring system that integrates advanced radar, high-resolution satellite sensors, and drones equipped with infrared and miniaturized radar technology. RSA enhances real-time detection and monitoring accuracy, even under extreme weather conditions. Beyond technology, the study emphasizes the importance of climate-adaptive defense policies and international cooperation among littoral states such as Indonesia, Malaysia, and Singapore to strengthen the resilience of maritime surveillance systems. RSA is presented as a strategic solution to ensure navigational safety, bolster regional maritime security, and maintain the continuity of global trade in increasingly climate-vulnerable environments